Women’s experiences of ceasing to breastfeed: Australian qualitative study - Jennifer Elizabeth Ayton; Leigh Tesch; Emily Hansen (BMJ Open)
Objective To investigate mothers’ infant feeding experiences (breastfeeding/formula milk feeding) with the aim of understanding how women experience cessation of exclusive breastfeeding.Design Multimethod, qualitative study; questionnaire, focus groups and interviews.Setting Northern and Southern Tasmania, Australia.Participants 127 mothers of childbearing age from a broad sociodemographic context completed a questionnaire and participated in 22 focus groups or 19 interviews across Tasmania, 2011–2013.Results Mothers view breastfeeding as ‘natural’ and ‘best’ and formula milk as ‘wrong’ and ‘unnatural’. In an effort to avoid formula and prolong exclusive breastfeeding, mothers will endure multiple issues (eg, pain, low milk supply, mastitis, public shaming) and make use of various forms of social and physical capital; resources such as father/partner support, expressing breast milk, bottles and dummies. The cessation of exclusive breastfeeding was frequently experienced as unexpected and ‘devastating’, leaving mothers with ‘breastfeeding grief’ (a prolonged sense of loss and failure).Conclusions and implications For many mothers, the cessation of exclusive breastfeeding results in lingering feelings of grief and failure making it harmful to women’s emotional well-being. Reframing breastfeeding as a family practice where fathers/partners are incorporated as breastfeeding partners has the potential to help women negotiate and prolong breastfeeding. Proactive counselling and debriefing are needed to assist women who are managing feelings of ‘breastfeeding grief’.